Organophosphate ester (OPEs) flame retardants and plasticizers in air and soil from a highly industrialized city in Turkey - Kurt Karakuş, Perihan Binnur; Alegria, Henry; Birgül, Aşkın; Gungormus, Elif; Jantunen, Liisa (Elsevier Science Bv, 2018)
Passive air samples were collected at eight sites in Bursa, Turkey during five sampling periods between February-December 2014. Locations encompassed urban, suburban, industrial, rural and background environments. Soil samples (n = 8) were collected at each site during February 2014. Six OPEs were detected in samples: tris(2-chloroethyl) phosphate (TCEP), tris(chloropropyl) phosphate (TCPP), triphenyl phosphate (TPHP), tris(2-butoxyethyl) phosphate (TBOEP), tris(2-ethylhexyl) phosphate (TEHP), and tris(2-isopropylphenyl) phosphate (T2-iPPP). Frequency of detection in air samples was TCPP and TPHP (100%) > TBOEP (88%) > TCEP (85%) > TEHP (78%) > T2iPPP (20%). Total OPEs in air per site by sampling period (excluding non-detects) ranged from 529 to 19,139 pg/m(3). In soil, total OPEs ranged from 38 to 468 ng/g dw. In air, alkylated OPEs dominated followed by halogenated and aryl OPEs. In air, annual mean concentrations were TBOEP > TCPP > TPHP > T2iPPP > TEHP > TCEP. In soils, alkylated OPEs were dominant at six sites and chlorinated OPEs at two sites. A comparison of OPE profiles between air and soil suggests that soils may be partly a source of OPEs to air. Mean concentrations in air were not directly proportional to temperature, and there were differences between alkylated compared to halogenated and aryl OPEs. In air, total and alkylated OPEs levels were fairly uniform, whereas more variability was found for the halogenated and aryl compounds. The relative contribution to total OPEs decreases for alkylated OPEs and increases for halogenated OPEs in samples going from background to suburban to urban and industrial sites. Levels of individual OPEs were all positively correlated between air and soils. In air, correlations between individual compounds were weak to moderate and were only statistically significant for TBOEP and TPHP. In soils, correlations were generally stronger and statistically significant only for TPHP and T2iPPP. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Organophosphate ester flame retardants; Plasticizers; Turkey; Environment; Urban; Suburban; Rural